Proton transport mechanism of imidazole, triazole and phosphoric acid mixtures from ab initio molecular dynamics simulations - Pahari, Swagata; Roy, Sudip (Physical Chemistry Chemical Physics, 2015)
We performed first principles molecular dynamics simulations to elucidate the mechanism and role of 1,2,3-triazole in proton transport while it is mixed with phosphoric acid (PA) and a phosphoric acid imidazole mixture. PA doped imidazole based polymer acts as an efficient polyelectrolyte membrane for fuel cells. The conductivity of this membrane increases when triazole is added to the system. For the first time we performed ab initio molecular dynamics simulations of complex mixtures of PA, imidazole and triazole. We have quantitatively estimated the structural diffusion and vehicular motion of protons. We found that upon the addition of triazole in PA and the PA imidazole mixture, the structural diffusion of protons increases significantly. The mechanism of proton transport is different when triazole is added to the mixture. We have also identified two different paths for structural diffusion (constructive and non-constructive) that contribute to long and short range proton transport.